An Uncoupling of Canonical Phenotypic Markers and Functional Potency of Ex Vivo-Expanded Natural Killer Cells - Lieberman, Nicole A. P.; DeGolier, Kole; Haberthur, Kristen; Chinn, Harrison; Moyes, Kara W.; Bouchlaka, Myriam N.; Walker, Kirsti L.; Capitini, Christian M.; Crane, Courtney A. (Frontiers in Immunology, 2018)
Recent advances in cellular therapies for patients with cancer, including checkpoint blockade and ex vivo expanded, tumor-specific T cells, have demonstrated that targeting the immune system is a powerful approach to the elimination of tumor cells. Clinical efforts have also illuminated limitations, however, including the potential for tumor cell antigenic drift and neoantigen formation, which promote tumor escape and recurrence, as well as rapid onset of T cell exhaustion in vivo. These findings suggest that antigen unrestricted cells, such as Natural Killer (NK) cells, may be beneficial for use as an alternative to or in combination with T cell based approaches. Although highly effective in lysing transformed cells, to date, few clinical trials have demonstrated anti-tumor function or persistence of transferred NK cells. Several recent studies describe methods to expand NK cells for adoptive transfer, although the effects of ex vivo expansion are not fully understood. We therefore explored the impact of a clinically approved 12-day expansion protocol using a K562 cell line expressing membrane bound IL-15 and 4-1BB ligand with high dose soluble IL-2 on the phenotype and functions of NK cells from healthy donors. Following expansions using this protocol, we found expression of surface proteins that implicate preferential expansion of NK cells that are not fully mature, as is typically associated with highly cytotoxic NK cell subsets. Despite increased expression of markers associated with functional exhaustion in T cells, we found that ex vivo expanded NK cells retained cytokine production capacity and had enhanced tumor cell cytotoxicity. The preferential expansion of an NK cell subset that is phenotypically immature and functionally pleiotropic suggests that adoptively transferred cells may persist better in vivo when compared to previous methods using this approach. Ex vivo expansion does not quell KIR diversity, allowing responsiveness to a variety of factors in vivo that may influence activation and inhibition. Collectively, our data suggest that in addition to robust NK cell expansion that has been described using this method, expanded NK cells may represent an ideal cell therapy that is longer lived, highly potent, and responsive to an array of activating and inhibitory signals.